Saliva versus Plasma Relative Bioavailability of Tolterodine in Humans: Validation of Class III Drugs of the Salivary Excretion Classification System - Idkaidek, N.; Najib, N.; Salem, I.I.; Najib, O. (Drug Research, 2016)
Relative bioavailability study of tolterodine in healthy human volunteers was done using saliva and plasma matrices in order to investigate the robustness of using saliva instead of plasma as a surrogate for bioavailability and bioequivalence of class III drugs according to the salivary excretion classification system (SECS). Saliva and plasma samples were collected up to 16 h after 2 mg oral dose. Saliva and plasma pharmacokinetic parameters were calculated by non compartmental analysis using Kinetica program V5. Human effective intestinal permeability was optimized by SimCYP program V13. Tolterodine falls into class III (High permeability/Low fraction unbound to plasma proteins) and hence was subjected to salivary excretion. A high pearsons correlation coefficient of 0.97 between mean saliva and plasma concentrations, and saliva/plasma concentrations ratio of 0.33 were observed. In addition, correlation coefficients and saliva/plasma ratios of area under curve and maximum concentration were 0.98, 0.95 and 0.42, 0.34 respectively. On the other hand, time to reach maximum concentration was higher in saliva by 2.37 fold. In addition, inter subject variability values in saliva were slightly higher than plasma leading to need for slightly higher number of subjects to be used in saliva studies (55 vs. 48 subjects). Non-invasive saliva sampling instead of invasive plasma sampling method can be used as a surrogate for bioavailability and bioequivalence of SECS class I drugs when adequate sample size is used.
Keywords: SECS; tolterodine; bioequivalence; pharmacokinetics; simCYP